The Use of Story Face Strategy to Enhance Reading Comprehension in Narrative Text - Mery Handrayani; Annisha Dyuli Adha; Rahma Dania (English Education and Applied Linguistics Journal (EEAL Journal), 2025)
This study investigates the use of the Story Face Strategy to enhance students’ reading comprehension of narrative texts at one of public junior high school in Padang. The research was motivated by students’ difficulties in understanding narrative texts, particularly in identifying the main idea, characters, setting, conflict, and resolution—common challenges faced by eighth-grade students. The objective of this study is to determine whether the implementation of the Story Face Strategy significantly enhances students’ reading comprehension. A one-group pre-test and post-test pre-experimental design was employed, with instruction delivered using the strategy across multiple sessions. Data were collected through a 25-item multiple-choice reading comprehension test administered before and after the intervention. The results showed a notable enhancement in students’ performance, with the average score increasing from 53.5 (pre-test) to 76.9 (post-test). A paired sample t-test confirmed the statistical significance of this improvement at the 0.05 confidence level. These findings suggest that the Story Face Strategy is effective in helping students understand narrative elements and can serve as an engaging and structured method for enhancing reading comprehension in junior high school contexts.